Diseño de un sistema integral de gestión para la comercialización de tecnologías domésticas en el Valle de los Chillos en el año 2013. - Capelo Flores, Andrea Elizabeth (2015)
In Ecuador there are few companies seeking continuous improvement, this due to the growing increase of external and internal competitors, who in their quest to become market leaders, evolve and adapt to new management trends, especially when it comes to market an innovative product in its field, with the case of domestic technology, applied to households in order to provide a unique user experience.